Economic Stability and Financing Quality: Key Determinants of Islamic Bank Growth - IQBAL, Muhammad; KURNIAWATI, Dian; RIDARMELLI, Ridarmelli; JUNAENI, Irawati (Theoretical and Practical Research in Economic Fields, 2025)
The significant increase in Islamic bank financing indicates a positive outlook for Islamic banks. The expansion of Islamic bank financing within a country should be analyzed independently from the country's overall economic climate. It is believed that uncertain economic conditions, such as economic growth, inflation, exchange rates, and interest rates, substantially impact financing disbursement in Islamic banks. This study aims to examine this relationship using Islamic banking data from Indonesia. The research utilizes time series data from January 2005 to December 2023 and employs VAR and VECM data analysis techniques. The research findings show that the primary factor driving the growth of Islamic bank financing is the quality of Islamic bank financing itself. In addition, the research findings also show that shocks in macroeconomic indicators, including economic growth, exchange rates, inflation, and interest rates, affect the growth of Islamic bank financing. Consistent economic growth supports the expansion of Islamic bank financing, while high volatility in economic growth hinders it. Likewise, a strong exchange rate and stable inflation are conducive to the growth of Islamic bank financing, thus accelerating the financing prospects. Therefore, the government plays a vital role in maintaining the growth of Islamic bank financing through financial stability, such as economic growth, exchange rates, and inflation.